2020
DOI: 10.1186/s12348-020-0200-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Susceptibilities of Methicillin-Susceptible and Resistant Staphylococci to Traditional Antibiotics Compared to a Novel Fluoroquinolone

Abstract: Background: To assess the in-vitro efficacy of delafloxacin, a new fourth generation fluoroquinolone, against Staphylococcus vitreous isolates from patients with clinically diagnosed endophthalmitis. This is the first investigation of delafloxacin in ocular tissues. Methods: Intravitreal isolates of culture-proven S. aureus and S. epidermidis were identified between 2014 and 2018. Minimum inhibitor concentrations (MIC) were determined using ETEST strips. The antibiotic susceptibilities were tested against a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“… 65 In a recent in vitro study comparing delafloxacin to levofloxacin, moxifloxacin and vancomycin against bacterial isolates from cases of endophthalmitis, delafloxacin showed significantly lower rates of resistance to S. epidermidis and S. aureus, including methicillin-resistant isolates, with low MICs. 66 Direct comparison with moxifloxacin across all the Staphylococcus isolates from this study demonstrated significantly increased susceptibility to delafloxacin. Delafloxacin has low (16%) protein binding, suggesting that its activity may not be significantly reduced in the inflamed cornea.…”
Section: Fluoroquinolonesmentioning
confidence: 69%
See 1 more Smart Citation
“… 65 In a recent in vitro study comparing delafloxacin to levofloxacin, moxifloxacin and vancomycin against bacterial isolates from cases of endophthalmitis, delafloxacin showed significantly lower rates of resistance to S. epidermidis and S. aureus, including methicillin-resistant isolates, with low MICs. 66 Direct comparison with moxifloxacin across all the Staphylococcus isolates from this study demonstrated significantly increased susceptibility to delafloxacin. Delafloxacin has low (16%) protein binding, suggesting that its activity may not be significantly reduced in the inflamed cornea.…”
Section: Fluoroquinolonesmentioning
confidence: 69%
“…Similar to the fourth generation FQs, delafloxacin is active against both bacterial gyrase and topoisomerase IV, reducing the risk of AMR 65. In a recent in vitro study comparing delafloxacin to levofloxacin, moxifloxacin and vancomycin against bacterial isolates from cases of endophthalmitis, delafloxacin showed significantly lower rates of resistance to S. epidermidis and S. aureus, including methicillin-resistant isolates, with low MICs 66. Direct comparison with moxifloxacin across all the Staphylococcus isolates from this study demonstrated significantly increased susceptibility to delafloxacin.…”
Section: Fluoroquinolonesmentioning
confidence: 99%
“…Increasing rates of resistance have been reported [21][22][23], and in this study, we showed 16.7% resistance across all isolates. Fourthgeneration fluoroquinolones, such as delafloxacin, demonstrate promising MIC effects in in-vitro studies and may be considered as adjunctive treatment in the future [24]. Some ophthalmologists use early systemic corticosteroids [1,13], with others concerned with inducing an immunosuppressive state.…”
Section: Discussionmentioning
confidence: 99%
“…All isolates were sensitive to ceftazidime, which is generally used as a first line intravitreal antibiotic along with vancomycin at this institution. Interestingly, isolates were pan-sensitive to fluoroquinolones tested, including delafloxacin, a newly registered fluoroquinolone not currently used in the treatment of ocular infections [ 22 ]. This resistance profile suggests there may be significant geographic variation, which may be better studied in larger cohorts.…”
Section: Discussionmentioning
confidence: 99%